2022
DOI: 10.3389/fphar.2022.917375
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect and Possible Mechanisms of Berberine in Diabetes-Related Cognitive Impairment: A Systematic Review and Meta-Analysis of Animal Studies

Abstract: Berberine, the main bioactive component of Coptis chinensis Franch., is widely used in the treatment of diabetes. Previous studies have reported that berberine supplementation may play a multitarget therapeutic role in diabetes-related cognitive impairment (DCI). This systematic review and meta-analysis evaluated the effect and possible mechanisms of berberine in animal models of DCI. Relevant studies were searched through PubMed, Web of Science, Embase, and three Chinese databases (CNKI, Wanfang, and VIP) unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…There are reasonable grounds to believe that reversing MCI to reduce the burden of dementia is a viable area of interest. There is compelling evidence to suggest that BBR was effective in improving cognitive function in Diabetes-related cognitive impairment and AD (Akbar et al, 2021;Hao et al, 2022). A spectrum of studies has demonstrated the ameliorative role of BBR in AD pathologies and cognitive dysfunction (He et al, 2017;Cai et al, 2018;Lin L. et al, 2020;Wu et al, 2021;Ye et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are reasonable grounds to believe that reversing MCI to reduce the burden of dementia is a viable area of interest. There is compelling evidence to suggest that BBR was effective in improving cognitive function in Diabetes-related cognitive impairment and AD (Akbar et al, 2021;Hao et al, 2022). A spectrum of studies has demonstrated the ameliorative role of BBR in AD pathologies and cognitive dysfunction (He et al, 2017;Cai et al, 2018;Lin L. et al, 2020;Wu et al, 2021;Ye et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…and Huang Qin (root of S. baicalensis Georgi), previously reported in LDXGT, were also present in BXXXT. Berberine, one of the main bioactive components of Huang Lian (root of C. chinensis Franch., a Chinese herb of BXXXT), has anti-diabetes-related cognitive impairment and anti-cognitive deficiency effects (Durairajan et al, 2012;Hao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, numerous studies demonstrated its weight loss ( Park et al, 2020 ), antihypertensive ( Ma et al, 2017 ), glucose-lowering ( Di et al, 2021 ), lipid-lowering ( Pirillo and Catapano, 2015 ), uric acid-lowering ( Li X. et al, 2021 ), anti-inflammatory ( Oshima et al, 2018 ; Lu et al, 2022 ), antifibrotic ( Ahmedy et al, 2022 ), antiproliferative ( Bonon et al, 2013 ), antiapoptotic ( Hu et al, 2012 ), antiaging ( Xu Z. et al, 2017 ), antioxidant ( Shou et al, 2022 ), antibacterial ( Liao et al, 2020 ), anticancer ( Liu et al, 2022 ), immunomodulatory ( Huang et al, 2021 ), gut microbiome adjustment ( Wang H. et al, 2022 ), neuroprotective ( Domitrović et al, 2013 ), cardioprotective ( Cai et al, 2021 ), and neuroprotective ( Shou et al, 2022 ) effects ( Figure 2 ). According to these pharmacological properties, BBR is promising in treating various diseases, such as MetS ( Och et al, 2022 ), hyperuricemia ( Li X. et al, 2021 ), acute kidney injury ( Shen et al, 2020 ), rheumatoid arthritis ( Huang et al, 2021 ), cardiovascular disease ( Feng et al, 2019 ), gastric cancer ( Liu et al, 2022 ), neuropsychiatric disorder ( Hao et al, 2022 ), and polycystic ovary syndrome ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%